2012
DOI: 10.1002/psc.2455
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell recovering effect of copper‐free GHK in skin

Abstract: The peptide Gly-His-Lys (GHK) is a naturally occurring copper(II)-chelating motifs in human serum and cerebrospinal fluid. In industry, GHK (with or without copper) is used to make hair and skin care products. Copper-GHK plays a physiological role in the process of wound healing and tissue repair by stimulating collagen synthesis in fibroblasts. We also reported that copper-GHK promotes the survival of basal stem cells in the skin. However, the effects of copper-free GHK (GHK) have not been investigated well. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Peled et al claimed that GHK increases proliferation of stem cells, while GHK‐Cu increases their progression into differentiated cells . Choi et al showed that GHK promotes the survival of basal stem cells in a skin equivalent model, and that the number of proliferating cells is also increased by the addition of GHK . The additional function of GHK‐Cu‐liposomes we found in this study was to enhance HUVECs proliferation by 33.1% compared with GHK‐Cu.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Peled et al claimed that GHK increases proliferation of stem cells, while GHK‐Cu increases their progression into differentiated cells . Choi et al showed that GHK promotes the survival of basal stem cells in a skin equivalent model, and that the number of proliferating cells is also increased by the addition of GHK . The additional function of GHK‐Cu‐liposomes we found in this study was to enhance HUVECs proliferation by 33.1% compared with GHK‐Cu.…”
Section: Discussionsupporting
confidence: 55%
“…22,23 Choi et al showed that GHK promotes the survival of basal stem cells in a skin equivalent model, and that the number of proliferating cells is also increased by the addition of GHK. 6 The additional function of GHK-Cu-liposomes we found in this study was to enhance HUVECs proliferation by 33.1% compared with GHK-Cu. ICP results indicated that although the Cu content delivered by GHK-Cu-liposomes is higher than that by free GHK-Cu, there is no big difference for the GHK-Cu uptake after 24 hours with liposome encapsulation.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Epidermal cells became more cuboidal, as is characteristic for stem cells. The authors concluded that GHK and GHK-Cu increased epidermal cell stemness and keratinocyte proliferation, also increasing p63 and integrin expression [48,49].…”
Section: Ghk Vs Ghk-cumentioning
confidence: 99%